Do health care physician need to risk their own lives? Time to change our own attitude towards recommended physical activity. (14th October 2021) - Memon, S; Khowaja, S; Shaikh, A; Memon, S; Bhatti, K; Saghir, T
Abstract: Background: Cardiovascular diseases are the leading cause of death around the world, South Asian population are at higher risk of atherosclerotic coronary artery diseases (CAD) comparatively. There is a recommended physical activity level to prevent atherosclerotic cardiovascular disease (ASCVD). Health care professionals especially doctors are main advisors to prescribe the exercise protocols among general population. Hence we conducted a survey among doctors of Pakistan to identify their physical activity as well as their knowledge and attitude toward recommended physical activity. Methodology: An online questionnaire was shared with doctors of various specialties working in private and public healthcare system of the Pakistan. It consisted of consent for participation, followed by information regarding demographic profile, preexisting co-morbid conditions, opinion regarding importance of physical activity to prevent ASCVD (5 point scale), perceived physical activity level (4 point scale), knowledge regarding ACC recommended physical activity level for primary prevention of ASCVD, lifestyle, and barriers in following recommended physical activity level. Collected data were entered and analyzed using SPSS version 21.0, participants were categorized into two groups as "cardiologists" and "non-cardiologists" and results were compared between the two groups. Results: A total of 159 doctors participated in the survey, out of whom 97 (61%) were cardiologist and remaining 62 (39%) were affiliated with other specialties. Male participants (72.3%) were predominant and mean age was 30.44±23.16 years. More than 60% (61.6%) of the participants were free of preexisting co-morbid condition, most common ASCVD risk factor was positive family history (26.4%) followed by smoking (7.5%) and hypertension (6.3%). According to BMI, 21.4% (34) were obese and 40.3% (64) were overweight. A total of 74.8% (119) of the participants claimed to know about ACC recommended physical activity level but 65.5% (78) were actually aware of recommended 150 min of moderate-intensity or 75 min of vigorous-intensity aerobic activity level. According to the lifestyle activities only 26.4% (42) of the participants were found to follow the ACC recommended physical activity level per week, this proportion was same between cardiologists and non-cardiologists, 25.8% vs. 27.4% respectively. Lack of time from daily routine (71.7%) was found to be most commonly stated reason for physical in activeness followed by overburden/over stress at workplace (33.3%) and lack of resources (14.5%). Conclusion: Knowledge and adherence to the ACC recommended physical actively level was poor among both cardiologists and non-cardiologists even after considering it important for the primary prevention of ASCVD. Majority of doctors were overweight and obese.Lake of time and resources and over stressed work life of doctors are the key barriers in following recommended physical activity level. FUNDunding Acknowledgement: Type of funding sources: None.